PROMOTING PARALINGUISTICS FEATURES THROUGH VOICEOVER CHALLENGES ON TIKTOK APPLICATION - Sudrajat, Indra; Amalia, Ridha (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2023)
The aim of the research is to find out how students promote paralinguistics features in TikTok voiceover and to investigate how TikTok can increase learner control over learning content and learner involvement in the content offered by the TikTok application. The rapid development of technology and communication (ICT) has made major changes in the world of education such as the TikTok application namely voice over Tiktok uses paralinguistics features to help respondents practice expression and intonation in their ability to play an event with confidence. In addition, each respondent has a different response to the learning content. At the first, they looked surprised, excited and challenged. Once they get to know Tiktok dubbing using deeper paralingustics features, they look more expressive, proficient, and confident. TikTok is believed to be able to promote elections that refer to various features on TikTok, such as TikTok voiceovers using paralinguistics features. The research instrument used to collect data was observation which consisted of two meetings which showed students' progress towards the content and also the participants' involvement in using the Tiktok application, the second interview which showed their responses to the content offered by the Tiktok application. The way that features paralinguistics features in Tiktok dub. The results of this study indicate that Tiktok makes a different contribution to each respondent.